A dimensão educativa da cooperativa popular - Denise Maria Maia (2009)
The central subject of this thesis is the educational dimension of a popular cooperative. This study aims to comprehend the actions of work and survival permeated by cooperative or competitive behaviors between members of popular cooperatives. The present research investigates a popular cooperative as an educational environment that is able to generate a citizen culture, to influence conceptions and behaviors, moreover it can provide and promote the transforming conditions in human being relations in a free and responsible way. Educational dimension is taken here as the association of relationships that build values. It is represented in the preparation and transformation of people cooperatively organized, according to the cooperative doctrine framework, to Paulo Freire and others. Concerning methodological approach, it was predominantly qualitative. The documents and interviews were analyzed through case study research of an enterprise that integrates the Extension Program of Federal University of Paraná related to the Technological Incubator of Popular Cooperatives. In order to identify the categories of educational dimension of popular cooperatives were chosen the sources connected to the case study used, in this case, Cooperativa de Embalagens Brasil (COEMBRA). For that, there was an attempt to capture the cooperative principles and values adopted in the world, the integrated management of the popular cooperatives first incubator as well mission and goals of the Paranaense Incubator. In this context it is possible to conclude that despite of failure in the economic dimension and incubation process problems, the popular cooperative was certainly able to raise and develop its ideal assimilation in its members, reflecting positively on their work and lives. This experience has influenced people because it has broadened their horizons; they were taken to think their lives and their relations in the world over, individual and collectively. They rescued their solidarity ideals and hopes; the will of taking new paths, searching a better life. They have been motivated by an institution inaccessible to them before: the university.